Pola Pengobatan Infeksi Saluran Pernafasan Akut (ISPA) Pasien Pediatrik Rawat Inap Di RRSUD Karanganyar Bulan November 2013-Maret 2014 - Mega Kusumanata; Susi Endrawati (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2013)
ABSTRACT: Background: Acute respiratory infection is an acute infection that attracks the respiratory tract (from nose to alveoli). It includes rhinitis, sinusitis, pharingitis, laryngitis, epiglotis, tonsilitis, otitis, bronchial infection on bronchus, broncholitis and pneumonia.Objective: The result to view description on the pattern of acute respiratory infection medication of the hospitalized pediatrict patients at the Local General Hospital of karanganyar in the month November 2013-March 2014, and determine compliance with the medication management guidelines of World Health Organization (WHO): Model Formulary for Children 2010 and the Ministry of Health of the republic Indonesia: Pharmaceutical Care for Respiratory Infection Disease 2005.Method: This research used non-experiment method with the descriptif non-analytical approach. The data of the research were the medical records of the hospitalized pediatric patients at the Local general hospital of Karanganyar who suffered from the acute respiratory infection.Result: The result of the research show that of the 32 padiatrict patient suffering from the acute respiratory infection, 53% are male and 47% are female. The therapies administered to the clients are principal therapy (antibiotics) and supportive therapy (simptomatics). The evaluation on the therapies shows that 91% the therapies are right dosage and 9% are not right dosage.Conclution: In general, the pattern of the medication administered to the pediatrict patients suffering from the ARI has been appropriate with the medication management guidelines of World Health Organization (WHO): Model Formulary for Children 2010 and the Ministry of Health of the republic Indonesia: Pharmaceutical Care for Respiratory Infection Disease 2005.Keywords: Acute Respiratory Infection (ARI), pediatrict, medication and infection.Â ABSTRAKSI: Latar Belakang: Infeksi saluran pernafasan akut (ISPA) adalah infeksi akut yang menyerang saluran pernafasan (hidung sampai alveoli). Infeksi saluran nafas akut meliputi rhinitis, sinusitis, faringitis, laryngitis, epiglotis, tonsilitis, otitis, infeksi pada bronkus, alveoli, bronkhiolitis dan pneumonia.Tujuan: Penelitian ini untuk melihat gambaran pola pengobatan pada kasus iSPA pasien pediatrik rawat inap di RSUD Karanganyar pada bulan November 2013-Maret 2014, dan mengetahui kesesuaiannya dengan pedoman penatalaksanaan menurut World Health Organization (WHO): Model Formulary for Children 2010 dan Depkes RI: Pharmaceutical Care untuk penyakit Infeksi Saluran Pernafasan 2005.Metode: Penelitian ini menggunakan penelitian Non Eksperimen dengan pendekatan deskriptif non analitik dan pengumpuan data retrospektif terhadap data rekam medis pasien ISPA pediatrik.Hasil: Hasil penelitian menunjukkan bahwa dari 32 kasus ISPA pediatrik, 53 % diantaranya pasien laki-laki dan sisanya 47 % perempuan. Terapi ISPA dilakukan dengan terapi pokok (antibiotik) dan terapi suportif (simptomatik). Evaluasi terapi menunjukkan bahwa 91 % tepat dosis dan 9 % tidak tepat dosis.Kesimpulan: Secara umum pola pengobatan pasien ISPA pediatrik telah sesuai dengan pedoman penatalaksanaan dari WHO: Model formulary for Children 2010 dan Depkes RI: Pharmaceutical Care untuk Penyakit Infeksi Saluran Pernafasan 2005.Kata Kunci: Infeksi Saluran Pernafasan Akut (ISPA), Pediatrik, Pengobatan, Infeksi.